1988
DOI: 10.1111/j.1365-2125.1988.tb05300.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of diazepam and midazolam as endoscopy premedication assessing changes in ventilation and oxygen saturation.

Abstract: 1 One hundred and two consecutive patients undergoing upper gastrointestinal endoscopy were randomised to be sedated with either intravenous diazepam (Diazemuls-Kabi Vitrum) or intravenous midazolam (Hypnovel-Roche). It was assumed that midazolam was likely to be approximately twice as potent as diazepam on the basis of previous work. 2 All patients had an ear oximeter attached throughout the procedure to record continuously their level of oxygen saturation. 3 All 102 patients had pre-endoscopy respiratory fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Significantly higher doses of analgesia were also required, potentiating the risks posed by the sedation. Thus, patients undergoing DBE may be at increased risk of hypotension, respiratory depression and even cardiorespiratory arrest 16 17…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher doses of analgesia were also required, potentiating the risks posed by the sedation. Thus, patients undergoing DBE may be at increased risk of hypotension, respiratory depression and even cardiorespiratory arrest 16 17…”
Section: Discussionmentioning
confidence: 99%
“…The RCT comparing the unsedated group and the midazolam‐alone or diazepam‐alone group showed that midazolam alone was more effective than diazepam alone in improving patient satisfaction and decreasing phlebitis . Six RCTs have directly compared midazolam and diazepam, and satisfaction for both patients and endoscopists was comparable between the two groups . Meanwhile, requesting the use of the same sedative and memory loss (the amnesia effect) during the examination were more frequently observed in the midazolam group than in the diazepam group.…”
Section: Statements On Sedation In Gastroenterological Endoscopymentioning
confidence: 99%
“…34 Six RCTs have directly compared midazolam and diazepam, and satisfaction for both patients and endoscopists was comparable between the two groups. [38][39][40][41][42][43] Meanwhile, requesting the use of the same sedative and memory loss (the amnesia effect) during the examination were more frequently observed in the midazolam group than in the diazepam group. Although there were no significant differences in adverse effects such as cardiorespiratory depression between the two groups, venous irritation (phlebitis) occurred significantly less frequently in the midazolam group than in the diazepam group.…”
Section: Commentarymentioning
confidence: 99%
“…The sedative used in most procedures in the present study was diazepam. Many randomized, controlled trials (RCTs) [8][9][10][11][12] have demonstrated that there is no difference in side effects such as cardiorespiratory depression between diazepam and midazolam when used during EGD procedures. When the recovery times of diazepam and midazolam were compared, midazolam was found to have a faster recovery 10 .…”
Section: Discussionmentioning
confidence: 99%